2022
DOI: 10.1021/acsomega.1c06638
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Cellular Uptake and Transcytosis of Peptide Nanoparticles in Spodoptera frugiperda Cells and Isolated Midgut

Abstract: Silencing genes in insects by introducing double-stranded RNA (dsRNA) in the diet holds promise as a new pest management method. It has been demonstrated that nanoparticles (NPs) can potentiate dsRNA silencing effects by promoting cellular internalization and protecting dsRNA against early degradation. However, many mysteries of how NPs and dsRNA are internalized by gut epithelial cells and, subsequently, transported across the midgut epithelium remain to be unraveled. The sole purpose of the current study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 63 publications
2
12
0
1
Order By: Relevance
“…Among these, clathrin-mediated endocytosis, caveolae-mediated endocytosis, and macropinocytosis are most commonly associated with transcytosis. [176] Inhibitors such as Filipin, [27,195] Nystatin, [196,197] Genistein, [198,199] and Indomethacin [200] are frequently employed to obstruct caveolae-mediated endocytosis, whereas Chloroquine, [201,202] Chlorpromazine, [198] and Dynasore [197,203] are typically used against clathrin-mediated endocytosis. Similarly, macropinocytosis is often inhibited by agents like Wortmannin, [204] Colchicine, [205,206] Imipramine, [207] 5-(N-Ethyl-N-isopropyl) amiloride (EIPA), [203,208] and Cytochalasin D. [197,209] For instance, in the research conducted by Fan, [210] endocytosis inhibition experiments indicated that NPs were internalized via caveolae-and macropinocytosis-related pathways, as evidenced by the reduced cellular uptake in the presence of their respective inhibitors.…”
Section: Methods To Investigate Transcytosismentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, clathrin-mediated endocytosis, caveolae-mediated endocytosis, and macropinocytosis are most commonly associated with transcytosis. [176] Inhibitors such as Filipin, [27,195] Nystatin, [196,197] Genistein, [198,199] and Indomethacin [200] are frequently employed to obstruct caveolae-mediated endocytosis, whereas Chloroquine, [201,202] Chlorpromazine, [198] and Dynasore [197,203] are typically used against clathrin-mediated endocytosis. Similarly, macropinocytosis is often inhibited by agents like Wortmannin, [204] Colchicine, [205,206] Imipramine, [207] 5-(N-Ethyl-N-isopropyl) amiloride (EIPA), [203,208] and Cytochalasin D. [197,209] For instance, in the research conducted by Fan, [210] endocytosis inhibition experiments indicated that NPs were internalized via caveolae-and macropinocytosis-related pathways, as evidenced by the reduced cellular uptake in the presence of their respective inhibitors.…”
Section: Methods To Investigate Transcytosismentioning
confidence: 99%
“…[176] Inhibitors such as Filipin, [27,195] Nystatin, [196,197] Genistein, [198,199] and Indomethacin [200] are frequently employed to obstruct caveolae-mediated endocytosis, whereas Chloroquine, [201,202] Chlorpromazine, [198] and Dynasore [197,203] are typically used against clathrin-mediated endocytosis. Similarly, macropinocytosis is often inhibited by agents like Wortmannin, [204] Colchicine, [205,206] Imipramine, [207] 5-(N-Ethyl-N-isopropyl) amiloride (EIPA), [203,208] and Cytochalasin D. [197,209] For instance, in the research conducted by Fan, [210] endocytosis inhibition experiments indicated that NPs were internalized via caveolae-and macropinocytosis-related pathways, as evidenced by the reduced cellular uptake in the presence of their respective inhibitors. Conversely, in Liu's study, [211] the use of various endocytosis inhibitors revealed that, except for nocodazole, which disrupts microtubule dynamics and blocks endocytic vesicle trafficking, all other inhibitors were ineffective in preventing cellular uptake of NPs.…”
Section: Methods To Investigate Transcytosismentioning
confidence: 99%
“…The protamine-lipid-dsRNA nanoparticles, according to a more recent study by Dhandapani et al (2022) , increase RNAi efficiency in the target insect species S. frugiperda by shielding dsRNA from nuclease degradation and thereby significantly increasing the stability of dsRNA in the organism. Similarly, according to McGraw et al (2022) , clathrin-mediated endocytosis and macropinocytosis account for the majority of cellular uptake, and once inside the midgut, transcytosis is involved in moving branched amphipathic peptide nanocapsules (BAPCs) dsRNA from the lumen to the hemolymph of S. frugiperda . RNAi bioinsecticide may not last long in the environment, so extra effort is needed to perform the spraying operation at the right time, which in turn challenges its adoption by growers ( Pedigo and Rice, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…Protein nanostructures, such as BAPCs, have been described as potentially more biocompatible and biodegradable than synthetic polymers, and more stable than those composed of lipids and polysaccharides [ 319 ]. They have been used to enhance the RNAi response in insects such as T. castaneum , Acyrthosiphon pisum [ 320 ], and Spodoptera frugiperda [ 321 ]. In the latter case, clathrin-mediated endocytosis and macropinocytosis uptake has been described, along with high endosomal escape and an increase in dsRNA transcytosis to hemolymph, improving the systemic response.…”
Section: Sources Of Dsrnas With Insecticidal Effectmentioning
confidence: 99%